Journal Geon Vol 4 No 1 January June 2017 (GEON Journal (Management, Organizations and Business), 2017)
Journal Geon Vol 4 No 1 January June 2017
Keywords: Entrepreneurship; Family Business; Strategy; Management; Innovation; marketing; Inclusive Business; Social Responsability